Pangek Sasau as Cultural Identity in an Expository-Style Documentary Film - Ikrar Qibran Wirja Nugraha; FX Yatno Karyadi; Fadly Rahmadanu; Muhammad Hamdanu Syakirin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study discusses the creation of an expository documentary film titled